2015
DOI: 10.2337/db15-0788
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin Antimicrobial Peptide: A Novel Regulator of Islet Function, Islet Regeneration, and Selected Gut Bacteria

Abstract: Cathelicidin antimicrobial peptide (CAMP) is a naturally occurring secreted peptide that is expressed in several organs with pleiotropic roles in immunomodulation, wound healing, and cell growth. We previously demonstrated that gut Camp expression is upregulated when type 1 diabetes–prone rats are protected from diabetes development. Unexpectedly, we have also identified novel CAMP expression in the pancreatic β-cells of rats, mice, and humans. CAMP was present even in sterile rat embryo islets, germ-free adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 49 publications
3
53
0
6
Order By: Relevance
“…Recent studies are beginning to delineate the mechanisms, by which innate immune systems interact with microbes in non-respiratory niches, such as the gastrointestinal tract. 7 The current study demonstrates, for the first time, an integrated role of LL-37 antimicrobial peptides (an important component of the innate immune system) and the airway microbiota in the pathogenesis of airway disease. Our data should facilitate further mechanistic investigations into this complex interplay.…”
Section: To the Editormentioning
confidence: 71%
See 1 more Smart Citation
“…Recent studies are beginning to delineate the mechanisms, by which innate immune systems interact with microbes in non-respiratory niches, such as the gastrointestinal tract. 7 The current study demonstrates, for the first time, an integrated role of LL-37 antimicrobial peptides (an important component of the innate immune system) and the airway microbiota in the pathogenesis of airway disease. Our data should facilitate further mechanistic investigations into this complex interplay.…”
Section: To the Editormentioning
confidence: 71%
“…5 In prior studies, serum cathelicidin level was inversely associated with disease severity in children with bronchiolitis, 6 and administration of LL-37 (the main active form of human cathelicidin) altered the microbiota in animal models. 7 We have previously demonstrated that, in a cohort of infants with severe bronchiolitis (bronchiolitis requiring hospitalization), 4 infants with a Haemophilus -dominant nasopharyngeal microbiota profile had higher severity; however, host immune responses were not examined. In the present study, we sought to determine interactions between serum LL-37 levels and nasopharyngeal microbiota profiles with regard to disease severity by using the data from a prospective cohort of infants with severe bronchiolitis.…”
Section: To the Editormentioning
confidence: 99%
“…Recent experiments suggest that M2 macrophages can prevent the onset of inflammatory response in T1D; such protection is likely mediated by secreted peptides with pro-proliferative, anti-inflammatory effects [57]. In particular, several studies focused on the heme oxygenase-1 (HO-1) pathway, whose induction confers protection from oxidative damage [58] and reduces the incidence of T1D in the BioBreeding diabetes-prone (BBdp) rat model [5961].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of TLR4 and CD14 is increased on LL-37-treated macrophages. Daily treatment of an inbred laboratory rat strain that spontaneously develops autoimmune type-1 diabetes with LL-37 results in enhanced β-cell neogenesis and upregulation of beneficial gut microbes [80]. In general, by inducing migration of neutrophils, monocytes and macrophages, eosinophils, and mast cells as well as prolonging the lifespan of neutrophils, cathelicidins directly modulate epithelial cell and keratinocyte responses to infecting pathogens [81].…”
Section: Human Cathelicidinsmentioning
confidence: 99%